Comparative techno-economic analysis of advanced biofuels, biochemicals, and hydrocarbon chemicals via the fast pyrolysis platform. Issue 1 (2nd January 2016) - Hu, Wenhao; Dang, Qi; Rover, Marjorie; Brown, Robert C.; Wright, Mark M.
ABSTRACT: This study evaluates the techno-economic feasibility of three product portfolios from a biomass fast pyrolysis biorefinery: biofuel, biochemicals, and hydrocarbon chemicals. The biorefinery design is based on the fast pyrolysis and five-stage fractionation system developed by Iowa State University. It can produce drop-in transportation fuels (biofuel scenario); infrastructure materials such as bioasphalt and bio-cement, and dextrose (biochemicals scenario); and hydrocarbon aromatics and olefins (hydrocarbon chemicals scenario). Bio-oil is fractionated into five stage-fractions and upgraded through different pathways based on the chosen portfolio. Minimum product-selling prices (MPSP) are calculated using a 30-year discounted cash flow rate of return analysis spreadsheet. Uncertainty analysis via Monte-Carlo analysis is used to determine the maximum investment cost (MIC) and the net present value (NPV) distribution. We estimate MPSPs of US3.09/gallon for biofuels, 433.7/MT for biochemicals, and 773.5/MT for hydrocarbon chemicals. The mean MICs are 162 MM, 610 MM, and 366.24 MM, and the net present value distributions are -243.42±268.9 MM, 503.83±429 MM, and 242.44±30.1. Biofuel, biochemical, and hydrocarbon chemical portfolios have 18%, 100%, and 100% chance that net present values are positive respectively, which indicates that producing biochemicals and hydrocarbon chemicals could be more competitive than producing biofuels alone.